PENGARUH TANAMAN INANG DAN MEDIA TANAM PADA PRODUKSI FUNGI MIKORIZA ARBUSKULAR - Maria Viva Rini; Vida Rozalinda (JURNAL AGROTROPIKA, 2010)
Host plant and medium are factors that affecting Abusrcular Mycorrhiza Fungi (AMF) production. Therefore, for maximum FMA inoculums production, four different host (mays, sorghum, Centrosema pubescens [CP], and Calopogonium mucunoides [CM]) and two medium (zeolit P-1 and zeolit P-3) were tested. The results showed that host from graminae (mays and sorghum) are better for AMF inoculums production as they gived higher root infection and spore production compared to legume (CP and CM). No significant effect was detected between P-1 and P-3, hence both medium can be used for AMF production. Furthermore, data obtained also showed that the effect of host on AMF production was not affected by medium used. Key words: Arbuscular Mycorrhiza Fungi, inoculums production, host, medium